Marriage Guidance in Maintaining Household Integrity in The Perspective of The Ministry Religion’s Officials in Pasuruan City - Ni’mah, Mufidatul (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Many prospective brides do not know the science of marriage, and how to have a good household causes the high divorce rate in Pasuruan City. To minimize the number of divorces, the Ministry of Religion of the City of Pasuruan requires each married couple to follow the Marriage Guidance program held by the Ministry of Religion. The purpose of the study was to determine to find out the marriage guidance implemented for prospective married couples in Pasuruan City and to find out the role of marriage guidance in maintaining household integrity in the perspective of Officials of the Ministry of Religion Pasuruan City. In this study, the author used empirical juridical research (field research) with the qualitative approach. As for the results of this study, the officials of the Pasuruan City Ministry of Religion agree that the marriage guidance program was very urgent because there are so many married couples who don't know the basis of marriage and weren't fluent in pronouncing the syahadah.